Acknowledging a Global Shift: A Primer for Thinking about Religion in Consumer Societies - Gauthier, François (Implicit religion, 2013)
The starting point of this article is the observation that the new form of cultural political economy, which has emerged in the last half of the twentieth century and become dominant since the 1980s, has had profound consequences for religious belief practice and expression worldwide. The rise of consumerism in the post-Second World War years, accompanied by the ever-growing and globalizing media-sphere, as well as the growing influence of neo-liberalism, have been pivotal in religious change. The article calls for work in this direction, and starts by a critical review of classical works on religion and economy, before surveying contemporary works, in a four-fold typology. Centering on consumerism, the article then argues that the rise of consumerism as a dominant cultural ethos, radicalizes the dynamics of identity and recognition that are typical of modern subjectivisation and community, which in turn shape contemporary religious phenomena.